Piglia y Saer, Theory and Praxis of the Novel - Casarin, Marcelo (Anales de Literatura Hispanoamericana, 2008)
The article correlates the main essayistic texts of Argentine narrators Juan José Saer and Ricardo Piglia, specially the writings that reflect upon novel and the ethical and esthettic options confronted by the genre; therefore, some of the topics dealt with in this work are: the novel as site of narrative experimentation, the discussion of its genre status and the tradition that each writer records in his literary production. Furthermore, this article intends to illustrate the dialogue between the two most outstanding narrators of the Argentine literary panorama in the last decades..
Keywords: Saer; Piglia; Novel; Theory; Narrative praxis